Hinduism Beliefs & Practices: Major Deities and Social Structures, Volume 1, by Jeaneane Fowler - Saul, R. Jeremy (Religions of South Asia, 2017)
Hinduism Beliefs & Practices: Major Deities and Social Structures, Volume 1, by Jeaneane Fowler. Brighton/Chicago/Toronto: Sussex Academic Press, 2014. x + 357 pp., £24.95 (pb). ISBN 978-1-84519-0622 (pb).